Implementation of Decision-Making Theory in Increasing Employee Professionalism - Taufiq Hidayah; Supiah Ningsih; Durahman Marpaung (International Journal of Economics (IJEC), 2022)
Writing about the theory of decision making is made with the aim of knowing and also getting to know how the management side of decision making is in a company and also an organization. The writing and research of the journal uses the method of reviewing literature studies taken from various writings, journals and also references which are national and international standards. Decision-making theory requires a series of structured and programmed processes that produce changes to the organization in a much better direction. In making this decision, it will set goals and objectives and identify problems. Then develop and determine alternatives in the decision-making process. The results of this study will later pay attention to several models or methods and also techniques for making the right decision to apply. From the research and also the elaboration of the literature review, it can be concluded that the decision-making process itself requires stages and steps that must be passed by all parties. By knowing the types of methods and techniques for making decisions that are appropriate and appropriate so as not to cause adverse factors. In practice, this decision-making should not be influenced by things that can make the decisions taken actually harm an organization. Decisions taken must be able to help organizations achieve their targets.